Promoting the use of evidence in health policymaking in the ECOWAS region: the development and contextualization of an evidence-based policymaking guidance - Chigozie Jesse Uneke; Issiaka Sombie; Ermel Johnson; Bilikis Iyabo Uneke; Stanley Okolo (BMC, 2020)
Abstract Background The Economic Commission of the West African States (ECOWAS), through her specialised health Institution, the West African Health Organization (WAHO) is supporting Members States to improve health outcomes in West Africa. There is a global recognition that evidence-based health policies are vital towards achieving continued improvement in health outcomes. The need to have a tool that will provide systematic guide on the use of evidence in policymaking necessitated the production of the evidence-based policy-making (EBPM) Guidance. Methods Google search was performed to identify existing guidance on EBPM. Lessons were drawn from the review of identified guidance documents. Consultation, interaction and interviews were held with policymakers from the 15 West African countries during WAHO organized regional meetings in Senegal, Nigeria, and Burkina Faso. The purpose was to elicit their views on the strategies to promote the use of evidence in policymaking to be included in the EBPM Guidance. A regional Guidance Validation Meeting for West African policymakers was thereafter convened by WAHO to review findings from review of existing guidance documents and validate the EBPM Guidance. Results Out of the 250 publications screened, six publications fulfilled the study inclusion criteria and were reviewed. Among the important issues highlighted include: what evidence informed decision-making is; different types of research methods, designs and approaches, and how to judge the quality of research. The identified main target end users of the EBPM Guidance are policy/decision makers in the West African sub-region, at local, sub-national, national and regional levels. Among the key recommendations included in the EBPM Guidance include: properly defining/refining policy problem; reviewing contextual issues; initiating policy priority setting; considering political acceptability of policy; commissioning research; use of rapid response services, use of policy advisory/technical/steering committees; and use of policy briefs and policy dialogue. Conclusion The EBPM Guidance is one of the emerging tools that can enhance the understanding of evidence to policy process. The strategies to facilitate the use of evidence in policymaking outlined in the Guidance, can be adapted to local context, and incorporated validated approaches that can be used to promote evidence-to-policy-to-practice process in West Africa.